PENGARUH RELATIONSHIP MARKETING DAN SERVICE QUALITY TERHADAP LOYALITAS KONSUMEN (STUDI PADA HOTEL DYAN GRAHA PEKANBARU) - Sormin, Fery Edwin Cesar; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted at Hotel Dyan Graha Pekanbaru, as for the purpose of this study was to determine the effect of integrated marketing communication and brand equity to costumer loyalty ( study at Hotel Dyan Graha Pekanbaru). Integrated marketing communication and brand equity as the independent variable (X1X2) while the costumer loyalty as the dependent variable (Y).The problem in this research is the sale of room service of Hotel Dyan Graha Pekanbaru fluctuated and tenden to decline each year, does not even reach the sales target. Seen from the presentation realization sale services of a hotel room in the last 5 years. The research sample was taken of 100 respondents of the population was calculated using the Slovin formula. The data was getting from the questionnaire and subsequently processed to then be tested with statistics through SPSS.From the results which shows that integrated marketing communications and brand equity have a positive and significant impact on customer loyalty (study at Hotel Dyan Graha Pekanbaru)Keywords: Integrated marketing communications, brand equity and customer loyalty.